Simulation and experimental study on ion current under GDI-HCCI combustion mode. (2016) - Cao, Yinbo; Chen, Yulin; Deng, Jun; Hu, Zongjie; Dibble, Robert W.; Li, Liguang
For a gasoline HCCI engine, the major challenge comes from the ignition and combustion control. Therefore, a feedback signal is necessary to detect combustion state and to realise closed-loop control of combustion process, and ionisation technology was studied for the purpose. The simulation results indicated that the 3D-CFD model could accurately predict in-cylinder pressure, heat release rate, ion profile, ion distribution and its generation mechanism. The experimental results showed that the fuel injection rate in NVO was of more significance to the HCCI combustion phase and the ion current, and HCCI combustion phase can be controlled by the fuel transmutation. In the wake of the excess air coefficient reducing, the amplitudes of the cylinder pressure and ion current were increased, and the phases were advanced. Under high load condition, the reduction of the throttle percentage caused increase in the fluctuation of the IMEP coefficient but weakness in the middle load.